1999
DOI: 10.1172/jci4765
|View full text |Cite
|
Sign up to set email alerts
|

Toxic bile salts induce rodent hepatocyte apoptosis via direct activation of Fas

Abstract: Cholestatic liver injury appears to result from the induction of hepatocyte apoptosis by toxic bile salts such as glycochenodeoxycholate (GCDC). Previous studies from this laboratory indicate that cathepsin B is a downstream effector protease during the hepatocyte apoptotic process. Because caspases can initiate apoptosis, the present studies were undertaken to determine the role of caspases in cathepsin B activation. Immunoblotting of GCDC-treated McNtcp.24 hepatoma cells demonstrated cleavage of poly(ADP-rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
329
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 505 publications
(350 citation statements)
references
References 41 publications
12
329
1
2
Order By: Relevance
“…Ligand-independent oligomerization was previously demonstrated for another death receptor, Fas. 30,31 For cancer gene therapy applications, strong cytotoxicity, exhibited by DR4 overexpression, required targeting. For this purpose, we used the promoter of the hTERT gene, which has been shown to be selectively active in cancer cells, [32][33][34][35] to drive DR4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand-independent oligomerization was previously demonstrated for another death receptor, Fas. 30,31 For cancer gene therapy applications, strong cytotoxicity, exhibited by DR4 overexpression, required targeting. For this purpose, we used the promoter of the hTERT gene, which has been shown to be selectively active in cancer cells, [32][33][34][35] to drive DR4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies suggest an involvement of the Fas receptor-mediated apoptotic pathway. Exposing rat hepatocytes to bile acids resulted in ligand-independent oligomerization of plasma membranebound Fas, recruitment of FADD, activation of caspase 8 and also a cascade of downstream caspases, and finally apoptosis [43]. Thus, since the Fas signaling pathway is functional in human colon cells [44], it is conceivable that NaDOC induced apoptosis in HCT-116 and HCT-15 cells in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that the intrahepatic accumulation of bile acids may directly or indirectly cause further damage to the liver [3] . One of the hypotheses regarding the pathophysiology of cholestasis is that accumulated hepatic bile acids directly induce cell apoptosis, as supported by studies on rat hepatocytes and human hepatoma lines [4,5] . Increasing attention has been paid the physiological role of bile acids acting as pro-inflammatory signals, which may trigger hepatic CXC chemokine formation during the development of cholestatic liver injury [6,7] .…”
Section: Introductionmentioning
confidence: 99%